2016
DOI: 10.1016/j.bbmt.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Pediatric Hematopoietic Stem Cell Transplantation Patients Despite Both Standard and Aggressive Supplementation

Abstract: We recently reported that more than 70% of pediatric and young adult patients had a vitamin D (VD) deficiency at the time of their hematopoietic stem cell transplantation (HSCT). Moreover, VD deficiency was associated with inferior survival at 100 days after transplantation. The goal of the present study was to evaluate the VD requirements needed to maintain an optimal VD level (30 to 60 ng/mL) during the first 3 months after transplantation using real-time VD monitoring and personalized VD supplementation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 20 publications
(22 reference statements)
4
28
0
Order By: Relevance
“…Despite high levels of year‐round sunlight, a high prevalence of suboptimal vitamin D levels (56%) was detected in children presenting for HSCT at our institution (Phoenix, AZ 33°N latitude). This finding further extends previous pediatric reports that the majority of pediatric patients have suboptimal vitamin D levels at time of HSCT 17–22 . Our data also showed an association between very low (<20 ng/ml) levels of vitamin D and reduced survival (see Fig.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Despite high levels of year‐round sunlight, a high prevalence of suboptimal vitamin D levels (56%) was detected in children presenting for HSCT at our institution (Phoenix, AZ 33°N latitude). This finding further extends previous pediatric reports that the majority of pediatric patients have suboptimal vitamin D levels at time of HSCT 17–22 . Our data also showed an association between very low (<20 ng/ml) levels of vitamin D and reduced survival (see Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Wallace et al. recently reported that despite giving a much higher than recommended vitamin D dose, more than 50% of their patients remained deficient …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of TA-TMA (and perhaps MBI-LCBI) in high-risk patients could be reduced by use of alternative transplant regimes (eg, reduced use of sirolimus and calcineurin inhibitors) or careful screening for TA-TMA and early institution of complement blockade [23]. In alternative strategies, we are currently studying dietary approaches to improve gut permeability and reduce MBI-LCBIs, including vitamins A and D, use of nondigestible oligosaccharides to maintain bowel microbiome diversity, and human behavior strategies to improve compliance with mouth care, another potential site of translocation [24,25]. …”
Section: Discussionmentioning
confidence: 99%